Analisis Performa Alat Bantu Pendaratan DVOR VB-53D dengan Ketepatan Periodisasi Kalibrasi pada Masa Pandemi COVID-19 di Airnav Cabang Batam - Hana Fatiha (Politeknik Penerbangan Makassar, 2022)
In order to maintain the performance of communication facilities and landing service facilities to remain operational, communication facilities and landing services such as DVOR must be calibrated periodically. How to find out how good the performance of flight navigation facilities to assist landing is by conducting ground inspections and flight inspections. The Director General of Hubud together with operators and the Airport Authority have coordinated to prevent the spread of COVID-19 including limiting activities for users, air transportation and technician activities in carrying out maintenance by conducting ground inspections. Ground testing or ground inspection can be an alternative extension when calibration is not carried out, but in the implementation of calibration there are several parameters that cannot be carried out at ground inspection and there are several possibilities that occur if calibration is not carried out on time. Then a survey and data processing was carried out using the SPSS application, the performance of the DVOR equipment can be seen from the results of data processing.